Efeitos colaterais do uso da ribavirina, prednisona e DMSO em cães naturalmente infectados pelo vírus da cinomose - Mangia, Simone H. [UNESP]; Moraes, Lívia F. [UNESP]; Takahira, Regina Kiomi [UNESP]; Motta, Rodrigo G. [UNESP]; Franco, Marília M.j. [UNESP]; Megid, Jane [UNESP]; Silva, Aristeu V.; Paes, Antonio Carlos [UNESP] (Colégio Brasileiro de Patologia Animal - CBPA, 2014)
The present study aims at the identification of undesirable effects of ribavirin, predinisone and DMSO in dogs naturally infected by canine distemper virus. The research analyzed 60 dogs with clinical neurological signs and 10 days of evolution. The animals were hospitalized for the appropriate support treatment; were daily observed, and complete blood cells count, biochemical analysis, and urine exam type I were conducted. Groups 1 and 2 were treated with ribavirin and its combination with DMSO; Groups 3 and 4 treated with prednisone and DMSO, Group 5 treated with ribavirin and prednisone, while Group 6 with ribavirin, prednisone and DMSO. Before the treatment, animals were anesthetized for the cerebrospinal fluid, bone marrow and blood samples collection for the diagnosis based on RT-PCR. The negative samples were analyzed using the hn-PCR technique. All the animals presented positive results in at least one of the 2 tests. The adverse result of ribavirin and its association with prednisone was characterized by haemolytic anemia, confirmed by the evaluation of bilirrubin occurrence only in the urine of dogs treated with ribavirin.

O estudo tem o objetivo de identificar efeitos indesejáveis da ribavirina, prednisona e DMSO em cães naturalmente infectados com o vírus da cinomose. Foram utilizados 60 cães apresentando quadro neurológico da cinomose com evolução de 10 dias. Os animais foram internados e receberam tratamento de suporte; foram avaliados diariamente e realizados hemograma, dosagem bioquímica e exame de urina tipo I. Os grupos 1 e 2 foram tratados com ribavirina e sua associação com DMSO; os grupos 3 e 4 com DMSO e prednisona e o grupos 5 com ribavirina e prednisona e o grupo 6 com ribavirina, prednisona e DMSO. Os animais foram anestesiados para a colheita de líquor, medula óssea e sangue, antes do tratamento para diagnóstico através da RT-PCR. As amostras negativas foram analisadas pela técnica de hn-PCR. Todos os animais apresentaram resultado positivo em pelo menos uma das duas reações. O efeito adverso da ribavirina e a sua associação com a prednisona foi a anemia hemolítica, que foi confirmada pela observação de bilirrubina na urina apenas dos cães tratados com ribavirina.
The side effects of ribavirin, prednisone and DMSO in dogs naturally infected by canine distemper virus
Keywords: Cinomose; ribavirina; prednisona; DMSO; efeitos indesejáveis; caninos; Canine distemper; ribavirin; DMSO; prednisone; undesirable effects; dogs